A Novel Pot-Economy Approach to the Synthesis of Triantennary GalNAc-Oligonucleotide - Artem Evgenievich Gusev; Vladimir Nikolaevich Ivanov; Nikolai Andreevich Dmitriev; Aleksandr Viktorovich Kholstov; Vladislav Aleksandrovich Vasilichin; Ilya Andreevich Kofiadi; Musa Rakhimovich Khaitov (Molecules)
N-Acetylgalactosamine (GalNAc) is an efficient and multifunctional delivery tool in the development and synthesis of chemically modified oligonucleotide therapeutics (conjugates). Such therapeutics demonstrate improved potency in vivo due to the selective and efficient delivery to hepatocytes in the liver via receptor-mediated endocytosis, which is what drives the high interest in this molecule. The ways to synthesize such structures are relatively new and have not been optimized in terms of the yields and stages both in lab and large-scale synthesis. Another significant criterion, especially in large-scale synthesis, is to match ecological norms and perform the synthesis in accordance with the Green Chemistry approach, i.e., to control and minimize the amounts of reagents and resources consumed and the waste generated. Here, we provide a robust and resource effective pot-economy method for the synthesis of triantennary GalNAc and GalNAc phosphoramidite/CPG optimized for laboratory scales.